Technological Options for Capturing and Reporting Parliamentary Proceedings (2014)
This practical handbook draws on the experiences and practices of several legislatures. It is intended to help parliaments to take informed decisions when developing their capacity to publish records of plenary and committee proceedings. It will be of particular interest to parliaments that do not yet publish their proceedings regularly or on a timely basis. It should also serve those that are looking to identify best practices and deliver better services